Trap‐Related Breakdown and Filamentary Conduction in Carbon Doped GaN. Issue 6 (19th February 2019) - Koller, Christian; Pobegen, Gregor; Ostermaier, Clemens; Hecke, Gebhard; Neumann, Richard; Holzbauer, Martin; Strasser, Gottfried; Pogany, Dionyz
Abstract : A breakdown phenomenon is studied in thin carbon doped GaN layers (GaN:C; carbon concentration 10 19 cm −3 ) embedded between a top metal electrode and bottom n‐doped GaN (n‐GaN). When slowly sweeping positive bias V at the top electrode up and down, a hysteresis is found with transitions to on‐ and off‐states at voltages V bd, up and V bd, down (< V bd, up ), respectively, and on‐ to off‐current ratios exceeding 10 3 . Breakdown at V bd, up occurs at an electric field of about 0.5 MV cm −1 in GaN:C. For V bd, down < V < V bd, up, transition to on‐state is time‐dependent with random time‐to‐breakdown in the ms to 10s range. Electroluminescence measurements in on‐state show conduction via multiple standing or slowly moving current filaments (CFs) which number and size increases with total current. The origin of an S‐shape I – V curve leading to hysteresis behavior is discussed in terms of trap‐related nonlinear generation‐recombination processes. Formation of multiple CFs is explained by spontaneous CF formation in a homogeneous spatially extended system composed of an active medium with S‐shape I – V curve (here GaN:C) connected in series with a passive layer (here n‐GaN). Unlike previous studies in various III‐N opto‐electronic systems, extended defects are supposed not to be responsible for the CF origin but just for their pinning. Abstract : Carbon doped GaN (GaN:C), embedded between a metal and n‐GaN layer, reveals S‐shape current–voltage characteristic with a negative differential resistance region. Transient electroluminescence analysis shows within a bistability region time‐dependent breakdown/transition from off‐ to on‐state with a current increase by a factor of 10³. This phenomenon is linked to the formation of multiple standing or slowly moving current filaments.